Личностные особенности обучающихся в сетевом информационном пространстве - Нина Л. Сунгурова (Problemy Wczesnej Edukacji)
The article deals with personality features of students in the information-psychological space. In this paper we present an analysis of the results of empirical research into the personality features of students with different orientations of networking and attitudes toward the Internet.